Outcome of Temporalis Myofascial Flap as an Interpositional Material in Temporomandibular Joint Ankylosis (Journal of Enam Medical College, 2022)
Temporomandibular joint ankylosis is a common problem in Bangladesh due to trauma and infection. Diverse interpositional materials have been proposed in this regard with especial advantages and limitation. Interpositional arthroplasty is the best solution. The aim of this review article is to provide a useful clinical update about interpositional arthroplasty in temporomandibular joint ankylosis, its advantages and limitations. For this purpose eighteen articles were selected through searching internet, reviewed and are summarized here. Dental surgeons need proper training for proper diagnosis and adequate treatment. Research in this field will be helpful for both patients and doctors. Temporomandibular joint ankylosis, treatment objectives of TMJ ankylosis and update of temporalis myofascial flap as an interpositional material are described here.J Enam Med Col 2020; 10(3): 186-189